Climate change affects cell‐wall structure and hydrolytic performance of a perennial grass as an energy crop. (16th November 2021) - de Freitas, Emanuelle N.; Khatri, Vinay; Contin, Daniele R.; de Oliveira, Tássio B.; Contato, Alex G.; Peralta, Rosane M.; dos Santos, Wanderley D.; Martinez, Carlos A.; Saddler, Jack N.; Polizeli, Maria de Lourdes T.M.
Abstract: Perennial grasses, such as Panicum maximum, are important alternatives to dedicated energy crops for bioethanol production. This study investigates whether future climate conditions could influence P. maximum cell‐wall structure and hydrolytic performance. To analyze interactions with environmental factors in field conditions, a combined Free‐air Temperature and CO2 Controlled Enhancement (Trop‐T‐FACE) facility was used to investigate the isolated and combined effect of elevated atmospheric CO2 concentration (eC) (600 μmol.mol −1 ) and elevated temperature (eT) by 2 °C more than the ambient temperature, on cell‐wall composition, cellulose crystallinity, accessibility, and hydrolysis yields. The elevated temperature treatments (eT and eT + eC) exhibited the most pronounced effects on the P. maximum cell wall. Warming reduced the starch content and the crystallinity index (CI) of cellulose and increased the cellulose content. Fluorescent protein‐tagged carbohydrate‐binding modules analysis demonstrated that warming improved total cellulose surface exposure/accessibility in eT and eT + eC by 181% and 132%, respectively. Consequently, glucan conversion yields were improved by 7.07% and 5.37%, showing that warming led to lower recalcitrance in P. maximum biomass, which positively affects its use in biorefineries. This work therefore provides important information from an ecological and economic point of view, allowing us to understand the mitigation process applied by this forage grass under future climate conditions. It might assist in selecting tropical forage grasses that are efficiently adapted to climate change, with a positive effect on bioenergy production. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd